Settlement of Inheritance of Customary Law Perspectives in Tapa District, Bone Bolango Regency, Gorontalo Province - Herno Dalali; Ajub Ishak (Al-Mizan (e-Journal), 2019)
This article discusses the settlement of inheritance to the people of Tapa District perspective of customary law. This research is a field study with data collection methods in the form of observations, interviews and documentation. The collected data were processed and analyzed qualitatively. The results show that: First, the settlement of the heirs to the people of Tapa District is divided into three, namely (1) deliberation negotiations between the two parties; (2) mediation by the District; and (3) apply to the Religious Court; Second: the factors of settlement in the Tapa District community, namely cultural and social factors, educational and economic factors.